Supporting functions of oligochitosan on soybean seed germination under normal and salinity stress conditions - Ngoc Lam, Pham Nguyen; Tam Nghi, Tran Duong; Quang Phat, Do; Bang Tuyen, Nguyen Thi; Huyen Tram, Nguyen Ngoc; Thi Hoang, Xuan Lan; Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2023)
Soybean is considered one of the important sources of oil and proteins worldwide. Nevertheless, the cultivation of soybeans is challenged by the threats of saline intrusion. Chitosan, a product derived from the shells of crustaceans such as shrimp, has been reported as a non-toxic biodegradable biopolymer that can minimize adverse impacts of salinity stress on plant growth. This study was to investigate the supportive activities of chitosan on germination under salinity stress of the local soybean cultivar MTD885-3. The assessment was conducted by pre-soaking soybean seeds in either distilled water, a commercial solution for seed germination, gibberellic acid 30 ppm, or oligochitosan solutions (500 ppm, 1000 ppm, and 2000 ppm), before allowing them to germinate in NaCl solution at different concentrations (0, 100, and 200 mM). As expected, soybean sprout emergence and growth were more adversely affected following the application of higher NaCl concentration. The pre-treatment of soybean seeds in oligochitosan solutions of 500 and/or 1000 ppm could enhance hypocotyl and radicle growth under both non-stressed and salinity conditions. Furthermore, seed pre-soaking with 1000 ppm oligochitosan could confer certain benefits for the soybean sprouts exposed to 200 mM NaCl treatment, which were also evidenced by shorter Mean Germination Time, higher Germination Index, and Coefficient of Velocity of Germination values. These findings indicate the practical application of chitosan in supporting the early growth of germinated seeds under osmotic stress conditions such as salinity.